Cardiac remodeling induced by smoking: concepts, relevance, and potential mechanisms - Minicucci, Marcos F. [UNESP]; Azevedo, Paula S.; Polegato, Bertha F.; Paiva, Sergio A. R.; Zornoff, Leonardo A. M. (Inflammation & Allergy Drug Targets, 2012)
Cardiac or ventricular remodeling is characterized by molecular, cellular, and interstitial alterations that lead to changes in heart size, mass, geometry and function in response to a given insult. Currently, tobacco smoke exposure is recognized as one of these insults. Indeed, tobacco smoke exposure induces the enlargement of the left-sided cardiac chambers, myocardial hypertrophy, and ventricular dysfunction. Potential mechanisms for these alterations include hemodynamic and neurohormonal changes, oxidative stress, inflammation, nitric oxide bioavailability, matrix metalloproteinases and mitogen-activated protein kinase activation. This review will focus on the concepts, relevance, and potential mechanisms of cardiac remodeling induced by tobacco smoke.
Keywords: Matrix metalloproteinases; Oxidative stress; Tobacco smoke exposure; Ventricular remodeling; Cardiac Remodeling; Heart size; Myocardial hypertrophy; Ventricular dysfunction; Hemodynamic; Neurohormonal changes; Oxidative stress; Inflammation; Mitogen-activated protein kinase activation